Ruh Hidup dalam Jasad Kaku: Mengenang Peran Intelektual Jaringan Islam Liberal (JIL) dalam Diskursus Islam Indonesia - Media Zainul Bahri (ILMU USHULUDDIN, 2015)
This esssay describes the Islamic main ideas of Jaringan Islam Liberal/JIL(Liberal Islam Network) since its beginning till the golden age of the first period(2001-10.) Although some scholarsstate that the religious view of JIL is unoriginal, but it is an interesting phenomenon in which it gave a significant contribution to Indonesian Islam. The article is ended with an explanation of the dim factors of JIL movement and the possibility of its future.